The Bridge Between Classical and “Synthetic”/Chemical Psychoses: Towards a Clinical, Psychopathological, and Therapeutic Perspective - Orsolini, Laura; Chiappini, Stefania; Papanti, Duccio; De Berardis, Domenico; Corkery, John M.; Schifano, Fabrizio (Frontiers in Psychiatry, 2019)
The critical spread and dissemination of novel psychoactive substances (NPS), particularly among the most vulnerable youngsters, may pose a further concern about the psychotic trajectories related to the intake of new synthetic drugs. The psychopathological pattern of the “new psychoses” appears to be extremely different from the classical presentation. Therefore, clinicians need more data on these new synthetic psychoses and recommendations on how to manage them. The present mini-review aims at deepening both the clinical, psychopathological features of synthetic/chemical NPS-induced psychoses and their therapeutic strategies, according to the different NPS classes implicated, by underlining the main differences with the “classical” psychoses. A comprehensive review was conducted using the PubMed/Medline database by combining the search strategy of free-text terms and exploding a range of MESH headings relating to the topics of novel psychoactive substances and synthetic/chemical psychoses as follows: (Novel Psychoactive Substances[Title/Abstract]) AND Psychosis[Title/Abstract]) and for each NPS categories as well, focusing on synthetic cannabinoids and cathinones, without time and/or language restrictions. Finally, an overview of the main clinical and psychopathological features between classical versus NPS-induced chemical/synthetic psychoses is provided for clinicians working with dual disorders and addiction psychiatry. Further insight is given here on therapeutic strategies and practical guidelines for managing patients affected with synthetic/chemical NPS-induced psychoses.